Life cycle assessment (LCA) and embodied carbon in energy and heat supply systems - Babich, T.; Buyak, N.; Sukhodub, I.; Deshko, V. (Energy and Automation, 2026)
Life Cycle Assessment (LCA) is one of the key tools for evaluating the environmental performance of energy and heating systems in the context of global decarbonization. In the context of the transition to highly efficient and renewable energy sources, it is becoming increasingly important to assess not only operational emissions, but also embodied carbon associated with the production, transportation, installation, maintenance, and disposal of materials and equipment. The purpose of the article is to summarize current scientific and methodological approaches to the application of LCA for heat supply, energy supply, and building engineering systems, as well as to analyze the role of embodied carbon in shaping the total environmental impact throughout the life cycle. Special attention is paid to methodological features of determining system boundaries, functional units, and interpreting LCA results. The research methods are based on a systematic analysis of international standards, scientific publications, and industry reports on LCA, whole-life carbon, and the assessment of environmental performance of energy systems. Approaches to assessing centralized heat supply, heating, ventilation, and air conditioning systems, as well as technologies using renewable energy sources, are analyzed. Along with global warming potential, indicators such as primary energy consumption, natural resource use, water footprint, waste generation, acidification potential, and eutrophication potential are considered. The results of the generalization show that with a decrease in operational emissions, the share of embodied carbon in the total environmental impact increases and can constitute a significant part of the total life cycle of energy systems. The conclusions can be used as a methodological basis for improving approaches to the design, modernization, and strategic planning of energy infrastructure decarbonization. Recieved: 03.01.2026. Recieved: 15.03.2026. Accepted: 17.04.2026.